2010
DOI: 10.1136/emj.2008.070284
|View full text |Cite
|
Sign up to set email alerts
|

Standard operating procedures as a tool to improve medical documentation in preclinical emergency medicine

Abstract: In this EMS base, developing SOPs is an effective tool to improve the quality of PCRs and the rate of completion of documentation items. Check boxes on PCR forms seem to have an important impact as they prompt the initial assessment, treatment and documentation of the actions taken during an EMS call. Consequently, SOPs and check boxes may serve to improve the transition of important information to emergency department staff, and thus contribute to improved patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 10 publications
0
13
1
3
Order By: Relevance
“…In contrast, these highly trained and experienced crews seldom reported exact values of RR - the air ambulance record templates only contained fields for RR RTS category, which was reported in 80% of cases. Francis et al found GCS and RR measurements in 80 - 90% of records and SBP measurements in 70% of records from physician-manned ground ambulances [27]. In contrast, the EMT/paramedic-manned ground ambulances in our study only documented exact values of GCS and SBP in 48% and 53% of records, respectively.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…In contrast, these highly trained and experienced crews seldom reported exact values of RR - the air ambulance record templates only contained fields for RR RTS category, which was reported in 80% of cases. Francis et al found GCS and RR measurements in 80 - 90% of records and SBP measurements in 70% of records from physician-manned ground ambulances [27]. In contrast, the EMT/paramedic-manned ground ambulances in our study only documented exact values of GCS and SBP in 48% and 53% of records, respectively.…”
Section: Discussioncontrasting
confidence: 65%
“…Design and layout of data collection forms has been shown to prompt users to record data in a specific way, the documentation rates for prompted items being higher than for non-prompted items [20,27]. In the anaesthesiologist-manned air ambulance service exact GCS scores and SBP measurements were documented in 89% and 84% of records respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, 3 months after the introduction of the SOP, a second series of 520 PMRs was collected from 520 consecutive scene calls. The PMR forms used in this EMS base (NADOK protocols; Datapec, Pliezhausen, Germany) contained check boxes covering the majority of data relevant to the patient's condition, as well as blank spaces to report further relevant patient data at the discretion of the emergency physician as described previously [4]. A mandatory form field is the diagnosis field.…”
Section: Study Protocol Measurements and Data Analysismentioning
confidence: 99%
“…Francis et al demonstrated that implementing an SOP for the pre-hospital treatment of acute coronary syndrome in the same physician-staffed EMS in Berlin improved some aspects of patient care, whereas other aspects were not affected [6]. The same research group also found that introducing an SOP for patient documentation did improve the quality of the patient care reports [7]. Martinon et al from the physician-staffed Service d’Aide Médicale Urgente (SAMU) in Paris reported that the implementation of an SOP for pre-hospital rapid sequence intubation (RSI) and post-RSI treatment of children with severe traumatic brain injury (TBI) significantly improved quality of care on several, but not all quality indicators [8].…”
Section: Introductionmentioning
confidence: 99%